Simulations of solid particle in a lid-driven cavity flow using Lattice Boltzmann method - Nik Mu’Tasim, Muhammad Ammar (2010)
The purpose of this study is to investigate the behaviour of a solid particle suspended in a two-dimensional viscous flow. The flow considered takes place in a closed square cavity, driven along its upper face by a translating lid. Second order upwind Lattice Boltzmann method computations are performed to characterize the fluid flow. The center locations of the fluid flow are first being track to simulate the path of the solid particle before the particle are introduced. The particle phase was modelled using the Lagrangian–Lagrangian (L–L) approach where the solid particles are treated as points moving in the computational domain as a result of the fluid motion. Slightly buoyant solid particle are then inserted in the cavity with flow at steady state condition. Different cases were considered, where the Reynolds number of the flow ranging in 130, 470, 860 and 3200 were used. The calculated solid particle motions are then compared with slightly denser particle with Reynolds number of 470. The results obtain shows that the slightly denser particle tends to move slightly downwards in the two-dimension cavity than the slightly buoyant particle. Solid particle trajectories are otherwise found to align closely with center location of the transient flow. The solid particle orbits, however, are not evenly distributed within the cavity, and gathered closer to the edge of the cavity as the Reynolds and Stokes numbers increase.